2018
DOI: 10.3892/or.2018.6907
|View full text |Cite
|
Sign up to set email alerts
|

miR‑138‑5p modulates the expression of excision repair cross‑complementing proteins ERCC1 and ERCC4, and regulates the sensitivity of gastric cancer cells to cisplatin

Abstract: The microRNA (miR)-138-5p affects the chemotherapeutic sensitivity of several human cancer types. In the present study, the expression and regulatory mechanisms of miR-138-5p were investigated in the gastric cancer cell line SGC7901 and its cisplatin-resistant derivative SGC7901/DDP. Gene microarray and reverse transcription-quantitative polymerase chain reaction analyses revealed that miR-138-5p was expressed at significantly lower levels in SGC7901/DDP compared with SGC7901 cells. Using computational predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The excision repair cross-complementation group (ERCC) is known to participate in the nucleotide excision repair (NER) pathway [57]. Recent evidence suggested that miR-138-5p reverses drug resistance in gastric cancer cells as a result of targeting ERCC1 and ERCC4 genes [58] (Table 2). Additionally, several studies demonstrated that miR-138-5p is a tumor suppressor and suppresses the growth and metastasis of cancer cells [59,60].…”
Section: Mir-138-5pmentioning
confidence: 99%
“…The excision repair cross-complementation group (ERCC) is known to participate in the nucleotide excision repair (NER) pathway [57]. Recent evidence suggested that miR-138-5p reverses drug resistance in gastric cancer cells as a result of targeting ERCC1 and ERCC4 genes [58] (Table 2). Additionally, several studies demonstrated that miR-138-5p is a tumor suppressor and suppresses the growth and metastasis of cancer cells [59,60].…”
Section: Mir-138-5pmentioning
confidence: 99%
“…MiRNAs are a class of sncRNAs of 19-24 nt in length, which could post-transcriptionally suppress gene expression via binding to the 3'-untranslated region (3'-UTR) of multiple target messenger RNAs (mRNAs) and/or other RNAs [42,43]. Multiple miRNAs are dysregulated in gastric cancer and play a crucial role in tumorigenesis, cancer metastasis, as well as development of resistance to drugs and radiation [44][45][46][47][48]. It has been observed that significantly changed miRNA expression profiles in drug-resistant gastric cancer cells compared to those in drug-sensitive cells.…”
Section: Mirnas and Drug Resistancementioning
confidence: 99%
“…Similarly, tumor suppressor miR-362-5p, miR-198, miR-574-3p, miR-876-3p, miR-874 and let-7b have been reported to reverse DDP resistance of gastric cancer cells via silencing suppressor of zeste 12 protein (SUZ12), fibroblast growth factor receptor 1 (FGFR1), zinc finger E-box binding homeobox transcription factor 1 (ZEB1), TMED3, autophagy-related 16-like 1 (ATG16 L1) and AURKB, respectively [117][118][119][120][121][122]. In addition, via targeting excision repair cross-complementing (ERCC), exogenous over-expression of tumor suppressor miR-122, miR-138-5p and miR-192-5p could also reverse DDP resistance of gastric cancer [48,123,124].…”
Section: Mirnas and Resistance To Platinum Drugsmentioning
confidence: 99%
“…In GAC, changes in ERCC1 expression have been associated with miR-122 and miR-139-5p, whose expression is reduced in cisplatin-resistant cells and inversely correlated with that of ERCC1. When both miRNAs were induced in vitro, ERCC1 protein levels decreased, and the sensitivity to cisplatin was restored [90,91].…”
Section: Mechanisms Of Chemoresistance Type 4 (Moc-4)mentioning
confidence: 99%
“…ERCC4 (or XPF), which forms a heterodimer with ERCC1 to repair DNA, has also been associated with GAC chemoresistance. In vitro studies have suggested that ERCC4 expression could be modulated by several miRNAs, inducing cisplatin resistance in GAC cells [91,99]. However, the few clinical studies performed up to date have not found a link between ERCC4 expression [45] or its genetic variants [104] with the sensitivity to platinum-containing drugs.…”
Section: Mechanisms Of Chemoresistance Type 4 (Moc-4)mentioning
confidence: 99%